2000
DOI: 10.1128/aem.66.7.2921-2927.2000
|View full text |Cite
|
Sign up to set email alerts
|

Antibiosis between Ruminal Bacteria and Ruminal Fungi

Abstract: Cellulose digestion, bacterial numbers, and fungal numbers were monitored over time in vitro by using a purified cellulose medium with and without antibiotics (penicillin and streptomycin). All fermentations were inoculated with a 1:10 dilution of whole rumen contents (WRC). Without antibiotics, cellulose digestion was higher (P < 0.01) at 24, 30, 48, and 72 h; fungi had almost disappeared by 24 h, while bacterial concentrations increased over 100-fold in 24 h and then decreased gradually up to 72 h. In those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…The cycle of metabolic changes in the rumen has made it possible to identify microbes commonly occurring in it, as well as to determine the ecological interactions taking place between populations (8). The most active ruminal microorganisms are cellulolytic bacteria, mainly of the genera Ruminococcus and Fibrobacter, as well as fungi and protozoa.…”
Section: Effect Of Balanced Supplementary Feeding In Wintermentioning
confidence: 99%
See 1 more Smart Citation
“…The cycle of metabolic changes in the rumen has made it possible to identify microbes commonly occurring in it, as well as to determine the ecological interactions taking place between populations (8). The most active ruminal microorganisms are cellulolytic bacteria, mainly of the genera Ruminococcus and Fibrobacter, as well as fungi and protozoa.…”
Section: Effect Of Balanced Supplementary Feeding In Wintermentioning
confidence: 99%
“…The total number of bacteria in the rumen fluid ranges from 10 9 to 10 12 cells/ml (10,15). Rumen protozoa, which are mainly ciliates, are usually classified on the basis of characteristics of their morphological structure, such as the location of the cilia or the number of skeletal plates (8,10). The number of protozoa in the rumen can reach 10 6 cells/ml and may account for as much as half of the microbial mass in the rumen (15,21).…”
Section: Effect Of Balanced Supplementary Feeding In Wintermentioning
confidence: 99%
“…A co-culture of two species will become self-regulating and stable if the specific growth rate of the faster-growing species is higher than that of the slower-growing species when [P] is zero. Knowledge on various inhibitory factors produced by micro-organisms in the rumen is limited (Dehority & Tirabasso, 2000). Bacteriocins (antibacterial peptides and proteins characterized by their ability to inhibit strains of bacteria) may have a key role in bacterial population dynamics (Riley, 1998).…”
Section: Microbial Interactions In Vitromentioning
confidence: 99%
“…These microorganisms are found regularly distributed in the fluid fraction or adhered to a solid material like the rumen walls. Dehority and Tirabasso (2000) observed that in ruminal content are found flagellate microorganisms that are believed to be flagellate protozoan. On the other hand, a series of studies done by Orpin (1974) established that these microorganisms as flagellate zoospores originating from anaerobic fungi.…”
Section: Introductionmentioning
confidence: 99%